Kijken is bekeken worden. Uit de kelders van het Stedelijk. - Komrij, Gerrit 1944-2012; Stedelijk Museum, Amsterdam (Amsterdam : Arbeiderspers, 1996)
Allebé, August ; Bakker-Korff, Alexander H. ; Beekman, Christiaan H. ; Bogaerts, Jan ; Breitner, George Hendrik ; Briët, Arthur H.C. ; Brusselmans, Jean ; Buning, Johan ; Campendonk, Heinrich ; Chagall, Marc ; Clemente, Francesco ; Cohen, Moos ; Corot, Jean-Baptiste Camille ; van Doesburg, Theo ; van Dongen, Kees ; Ensor, James ; Erfmann, Ferdinand G. ; Fernhout, Edgar ; Freijmuth, Alphons ; Garf, Salomon ; Gestel, Leo ; Gordijn, Herman ; Grauss, G.H. ; Hart-Nibbrig, Ferdinand ; Haverman, Hendrik ; van Hell, Johan ; van der Hem, Pieter ; Hendriks, Sara F. ; van Hoijtema, Theo ; Houtman, Sipke C. ; Huszar, Vilmos ; Israels, Isaac ; Israëls, Jozef ; Jbzn., Willem Matthijs Maris ; Ket, Dick ; Kever, Jacob ; Kirchner, Ernst Ludwig ; Knap, Josina ; Landkroon, Piet ; van Looy, Jacobus ; Luns, Huib ; Maks, Kees ; Mankes, Jan ; Millet, Jean-François ; Molkenboer, Theodorus ; Monnickendam, Martin ; Net, Gerrit van 't ; Neuman, Clasine ; Niehaus, Kasper ; Noij, Toon ; Oepts, Wim ; Oijens, David ; Onnes, Harm Kamerlingh ; Ouborg, Piet ; Pascin, Jules ; Perné, Gust van de Wall ; Ritsema, Coba ; de Roode-Heijermans, Marie ; Scheltema, Taco ; Schlemmer, Oskar ; Schumacher, Wim ; Schwartze, Thérèse ; Sluijters, Jan ; Smorenberg, Dirk ; Spencer, Stanley ; Tholen, Willem Bastiaan ; Thorn Prikker, Johan ; Toorop, Charley ; Toorop, Jan ; Verster, Floris H. ; Verwey, Kees ; Visser, Jan ; Werkman, Hendrik N. ; Wiegers, Jan ; Willink, Carel ; Witsen, Willem
boek